A prospective, single centre, observational study to evaluate the perception, knowledge and awareness about anaesthesia and role of anaesthesiologists, preoperatively and postoperatively, among patients undergoing anaesthesia procedure in tertiary care hospital - Tiwaskar, Shilpa; Shah, Kshama; Kulkarni, Vivek; Karande, Jyotsna (International Journal of Research in Medical Sciences, 2025)
Background: Anaesthesiologists play a vital role perioperatively. Little is known about this to the patients. Hence, we undertook the study to evaluate the perception, knowledge and awareness about anaesthesia and anaesthesiologists amongst patients coming for surgery. Methods: This study was an observational, interview questionnaire based; single centre study carried over 18 months from March 2017. 260 participants were asked about their perception and knowledge of anaesthesia and anaesthesiologist. The numeric data was summarized by descriptive statistics. Results: Study could be completed in 255 patients, out of which, 4.70% were illiterate, 53.72% were high-school graduates and 41.56% were graduates. Out of 243 literates, 39.6% were aware that anaesthesiologists are doctors and only 10.94% had the knowledge about anaesthesia. The fear factor about anaesthesia in illiterate, high school graduates and graduate groups were 27.82%, 26.81% and 26.87% respectively. Conclusions: Though the literacy level was 95.29% among our surgical patients, still 60.4% of patients were unaware of the role of anaesthesiologist and 89.06% were ignorant about knowledge of anaesthesia. All patients had some fear factor about anaesthesia, with an average of 27.28%, irrespective of gender and education level. The post-surgery questionnaire revealed that 98.82% of patients felt protected and cared for all throughout the perioperative period due to counselling during pre-anaesthesia visit.